The Development of Indonesian Marriage Law in Jakarta Governor Regulation No. 185 of 2017 - Jayusman, Jayusman; Jaya, Hervianis Virdya; Julir, Nenan; Hidayat, Rahmat (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
The Governor of DKI Jakarta regulates that any prospective bride and groom who intend to get married shall follow guidance and health checks. This policy is a condition for the implementation of marriage. The health checks carried out are not only Tetanus Toxoid vaccination, but also other health tests. If necessary, the doctor can provide a referral for further examination of medically found indications. The prospective bride and groom will then receive a marriage-worthy certificate. This certificate is one of the requirements to obtain the N1 form. This policy is significant leap taken by the Governor of DKI Jakarta. This present study concerns with the perspective of progressive law on DKI Jakarta Governor Regulation No. 185 of 2017 in the context of the development of Islamic family law in Indonesia. The study utilized library research approach with the descriptive analysis method. The primary data included the DKI Jakarta Governor Regulation No. 185 of 2017, and the secondary data were related literature. This study used the progressive legal theory and the Islamic law approach. The analysis and conclusion drawing were done deductively. The study revealed that the DKI Jakarta Governor Regulation No. 185 of 2017 is a progressive policy in preventing the transmission of infectious diseases among prospective brides and grooms, and in reducing maternal and infant mortality. This regulation shall bring goodness and benefit into domestic life, especially for the bridal couples and their descendants, as well as the society and nation. Further, the regulation shall give a positive impact on the development of marriage law in Indonesia.